2015
DOI: 10.1111/jgs.13702
|View full text |Cite
|
Sign up to set email alerts
|

American Geriatrics Society 2015 Updated Beers Criteria for Potentially Inappropriate Medication Use in Older Adults

Abstract: The 2015 American Geriatrics Society (AGS) Beers Criteria are presented. Like the 2012 AGS Beers Criteria, they include lists of potentially inappropriate medications to be avoided in older adults. New to the criteria are lists of select drugs that should be avoided or have their dose adjusted based on the individual's kidney function and select drug-drug interactions documented to be associated with harms in older adults. The specific aim was to have a 13-member interdisciplinary panel of experts in geriatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
898
5
58

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,153 publications
(999 citation statements)
references
References 42 publications
14
898
5
58
Order By: Relevance
“…These results demonstrate that hospitalized elderly may be at greater risk of ADRs such as constipation, orthostatic hypotension, sedation, walking difficulties, falls and fractures (18,19).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…These results demonstrate that hospitalized elderly may be at greater risk of ADRs such as constipation, orthostatic hypotension, sedation, walking difficulties, falls and fractures (18,19).…”
Section: Resultsmentioning
confidence: 82%
“…Pharmacotherapy is considered potentially inappropriate when the risks of its use outweigh its benefits (18)(19)(20).Exposure of the elderly population to this type of medication has been shown to be associated with increased morbidity and mortality, increased the frequency of health service use and higher occurrence of ADR (12,13,15,16,21,22).Studies have shown that the prescription of PIM to Brazilian elderly is commonplace in some different settings (23)(24)(25). However, the number of pharmacoepidemiological studies focusing on the Brazilian hospitalized elderly population during their hospital stay is small (26).…”
Section: Introductionmentioning
confidence: 99%
“…We anticipated that this project would generate a list of appropriate and inappropriate medications for managing co‐morbidities in dementia, similar to other existing explicit prescribing criteria in older people such as the Beers and STOPP/START criteria 60, 61. However, the expert responses to the Round 1 questions emphasised individualising treatment and the importance of reviewing treatments for co‐morbidities as the dementia progresses.…”
Section: Discussionmentioning
confidence: 99%
“…The Infectious Diseases Society of America and the European Society for Microbiology and Infectious Diseases recommend nitrofurantoin as one of the first line antibiotics in uncomplicated UTIs, given the low cost of therapy, efficacy as well as its positive impact on antimicrobial resistance patterns [1]. However, nitrofurantoin is also one of the most common drugs to be reported for a variety of pulmonary, hepatic and peripheral nervous system adverse effects [2][3][4]. The spectrum of pulmonary toxicities ranges from acute hypersensitivity reactions to chronic dose-dependent pathologies like chronic interstitial pneumonitis, fibrosis and organizing pneumonia [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…However, nitrofurantoin is also one of the most common drugs to be reported for a variety of pulmonary, hepatic and peripheral nervous system adverse effects [2][3][4]. The spectrum of pulmonary toxicities ranges from acute hypersensitivity reactions to chronic dose-dependent pathologies like chronic interstitial pneumonitis, fibrosis and organizing pneumonia [2][3][4]. In view of these possible side effects and available alternative medicines, the American Geriatrics Society in a 2015 update listed nitrofurantoin as a "potentially inappropriate medication" for prolonged use in adults 65 years of age and older [4].…”
Section: Introductionmentioning
confidence: 99%